Transient ischemic attack patients with fluctuations are at highest risk for erly stroke - Chatzikonstantinou, Anastasios; Willmann, Olaf; Jäger, Theodor; Szabo, Kristina; Hennerici, Michael G. (Cerebrovascular diseases, 2009)
Background: The management and risk of early stroke are unclear in patients with fluctuating neurological symptoms. We aimed to evaluate the clinical course of these patients presenting within 24 h after onset of acute cerebral ischemia symptoms. Methods: All patients with transient ischemic signs/symptoms consecutively admitted to our Emergency Stroke Unit were recruited. Patients were neurologically examined and underwent prompt CCT plus MRI imaging for visualization of early signs of ischemia. Results: Among 122 patients, 84 (69%) had single symptoms, 33 (27%) showed rapidly relapsing and remitting symptoms - in 5 cases (4%) symptom duration could not reliably be assessed. 11/122 (9%) suffered a stroke during hospitalization. ABCD2 scores did not predict early strokes: 2/11 (18.2%) were in the ‘lower risk’, 7/11 (63.6%) in the ‘moderate risk’ and only 2/11 (18.2%) in the ‘high risk’ group (p = 0.103). 3/11 patients (27.3%) revealed lesions in neuroimaging, but surprisingly 8/11 (72.7%, p = 0.132) did not. However, patients with fluctuations in neurological status were significantly more likely to suffer a stroke: 9/122 versus 2/122 with stable symptoms (p < 0.05). Patients with small vessel disease were common in all (53/ 122; 43.4%) and within those who suffered an early stroke (6/11; 54.5%). Conclusions: Patients with unstable transient ischemic attacks immediately after onset of clinical symptoms are at high risk for subsequent stroke - they may benefit from Stroke Unit management and potential early thrombolysis once they develop strokes.
Gesehen am 17.03.2021